Bio Analisis Kinerja dan Keberlanjutan Usaha Mie Instan Sehat Milicious di Kota Palembang - Natasya De' Angel; Cyntia Caroline Salim; Yulizar Kasih (Universitas Multi Data Palembang, 2026)
This study aims to analyze the implementation, business performance, and sustainability of Milicious, a healthy instant noodle enterprise in Palembang. The research employs a mixed-method approach combining quantitative and qualitative techniques. Quantitative data were collected through an online questionnaire distributed to 52 respondents and supported by financial statement analysis, including income statements and cash flow reports. Qualitative data were obtained through direct observation and interviews with the business owner. The analysis focuses on marketing mix strategy, financial performance, and business sustainability. The findings indicate that Milicious has demonstrated positive financial growth, effective marketing implementation, and strong consumer acceptance. Furthermore, product innovation based on natural ingredients provides competitive advantage and supports long-term sustainability. Therefore, Milicious shows significant potential for continued development in the healthy culinary market segment.